2016
DOI: 10.4103/2230-8210.179993
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of biphasic insulin aspart and biphasic insulin lispro mix in patients with type 2 diabetes: A review of the literature

Abstract: Type 2 diabetes (T2D) represents an escalating burden worldwide, particularly in China and India. Compared with Caucasians, Asian people with diabetes have lower body mass index, increased visceral adiposity, and postprandial glucose (PPG)/insulin resistance. Since postprandial hyperglycemia contributes significantly to total glycemic burden and is associated with heightened cardiovascular risk, targeting PPG early in T2D is paramount. Premixed insulin regimens are widely used in Asia due to their convenience … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
1
3
0
Order By: Relevance
“…The present indirect comparison between IDegAsp and IGlarLixi proposed a protective effect of the latter against weight gain. This observation is consistent with the literature [13,15,16], where IGlarLixi was not associated with weight gain, in contrast with fast-acting insulin combined with long-acting insulin [16][17][18]. In addition, gastrointestinal adverse effects reported with lixisenatide alone were alleviated in patients treated with IGlarLixi [15], further supporting the use of the combination formula.…”
Section: Discussionsupporting
confidence: 90%
“…The present indirect comparison between IDegAsp and IGlarLixi proposed a protective effect of the latter against weight gain. This observation is consistent with the literature [13,15,16], where IGlarLixi was not associated with weight gain, in contrast with fast-acting insulin combined with long-acting insulin [16][17][18]. In addition, gastrointestinal adverse effects reported with lixisenatide alone were alleviated in patients treated with IGlarLixi [15], further supporting the use of the combination formula.…”
Section: Discussionsupporting
confidence: 90%
“… Metformin reduces glucose production during the fasting state, while improves glucose use, which may not be the main postprandial factor; however, studies have shown that using Metformin and Glyburide reduces glucose levels after meals.  α-Glucosidase inhibitors reduce digestion and absorption of carbohydrates, lowering glucose levels after meals by 0.5%, but patients may have gastrointestinal side effects [75,76,77,80].  Amylin analog decreases postprandial blood glucose by glucagon suppression and delays gastric emptying time [78].…”
Section: Pharmacologic Interventionmentioning
confidence: 99%
“… Amylin analog decreases postprandial blood glucose by glucagon suppression and delays gastric emptying time [78].  Short-acting insulin [79] and rapid-acting insulin analog or premix insulin [80,81].  GLP-1 is a hormone secreted by intestinal L cells after eating, which increases the level of glucose-dependent insulin secretion through cyclic adenosine monophosphate-dependent protein kinase stimulation in the pancreas [82,83,84].…”
Section: Pharmacologic Interventionmentioning
confidence: 99%
“…Premixed insulins contain rapid-and intermediate-acting insulin that control fasting plasma glucose (FPG) and postprandial glucose (PPG) elevations, respectively [9]. In many Asian countries, premixed insulins are more widely used as a starter regimen than basal insulin analog (BI) [9,10].…”
Section: Introductionmentioning
confidence: 99%